Data supporting: 'Strain controlled fatigue behaviour of wire + arc additive manufactured Ti-6Al-4V' - Khadar Syed, Abdul; Williams, Stewart W. (Cranfield University, 2023)
This paper investigates the strain controlled fatigue and cyclic deformation behaviour of a wire + arc additive manufactured Ti-6Al-4V alloy in the as-built condition. Higher local heat input used to build the material exhibited a coarser parent columnar β grain structure along with a coarser transformation microstructure compared to other additive manufactured Ti-6Al-4V. Test specimens were manufactured in horizontal and vertical orientations with respect to the deposited layers. Property isotropy was observed at lower applied strain values. When the strain amplitude was above 0.6%, the vertical samples, where the loading axis was in parallel with the parent columnar β grains, showed marginally higher fatigue strength owing to larger plastic deformation. Moreover, higher cyclic softening ratio by a factor of two was measured in the vertical samples when the strain amplitude was above 0.6%. No porosity defects were found in the material. Cracks were initiated from α lath due to cyclic slip localisation.
Keywords: 'Low cycle fatigue'; 'Cyclic deformation'; 'Strain controlled fatigue'; 'Titanium alloys'; 'WAAM'